Response of bacterial community composition and co-occurrence network to straw and straw biochar incorporation - Du, Mingcheng; Zhang, Jianyun; Wang, Guoqing; Liu, Cuishan; Wang, Zhenlong (Frontiers in Microbiology, 2022)
Microbial decomposition plays a crucial role in the incorporation of straw and straw biochar (SSB) into soil. Lime concretion black soil (LCBS) is a typical low-medium crop yield soil, and it is also one of the main soil types for grain production in China. However, the link between SSB additions and soil bacterial communities in LCBS remains unclear. This study explored the effects of SSB incorporation on bacterial community composition, structure and co-occurrence network patterns at different soil depths and maize growth stages. The results showed that soil PH, soil organic matter and total nitrogen significantly affected the seasonality and stratification of the soil bacterial community. The composition and diversity of bacterial communities were significantly affected by growth period and treatment rather than soil depth. Specifically, the bacterial community diversity increased significantly with crop growth at 0–20 cm, decreased the relative abundance of Actinobacteria, and increased the relative abundance of Proteobacteria and Acidobacteria. SF (straw with fertilizer) and BF (straw biochar with fertilizer) treatments decreased bacterial community diversity. Co-occurrence networks are more complex in BF, S (straw), and SF treatments, and the number of edge network patterns is increased by 92.5, 40, and 60% at the maturity stage compared with F (fertilizer) treatment, respectively. Moreover, the positive effect of straw biochar on the bacterial network pattern increased with time, while the effect of straw weakened. Notably, we found that rare species inside keystone taxa (Gemmatimonadetes and Nitrospirae) play an indispensable role in maintaining bacterial network construction in LCBS. This study offers a comprehensive understanding of the response of soil bacterial communities to SSB addition in LCBS areas, and provides a reference for further improvement of LCBS productivity.